Huge Anterior Lip Cervical Fibroma Presenting as Gynaecological Emergency: A Rare Case Report - Khanam, Deeba; Hakim, Seema; Parveen, Shazia; Mohammad Ali, Wasif (International Journal of Medical Research and Review, 2015)
Leiomyoma are the most common tumours of female pelvis .These are mostly composed of smooth muscle cells and variable amount of tissues from extracellular matrix. Most of the fibroids are located in body of uterus but only 1-2% are located in cervix. We report a case of 35 year old female who presented to us with a big vaginal mass ,pain, difficulty in walking and excessive bleeding and clinically differential diagnosis of chronic inversion , infected cervical polyp, procidentia and cervical fibroid was made but after preoperative evaluation , surgery and histopathology report it was diagnosed as cervical fibroid. Pedunculated cervical fibroid is a rare entity and patient presenting in shock is unusual presentation as in our case where we did not have the time for proper investigation and immediate measures had to be taken for the management.